2023
DOI: 10.3389/ftox.2023.1157761
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the association between talc and female reproductive tract cancers

Heather N. Lynch,
Daniel J. Lauer,
Olivia Messina Leleck
et al.

Abstract: Talc is a hydrous magnesium sheet silicate used in cosmetic powders, ceramics, paints, rubber, and many other products. We conducted a systematic review of the potential carcinogenicity of genitally applied talc in humans. Our systematic review methods adhere to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and incorporated aspects from the US Institute of Medicine (IOM, now the National Academy of Medicine) and several US EPA frameworks for systematic reviews, evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
(227 reference statements)
0
5
0
Order By: Relevance
“…This was motivated by reviews and meta-analyses reporting different results by study design ( e.g. , [ [7] , [8] ]) and the recent availability of data on talc recall in the prospective Sister's Study [ 13 ]. Realistically, the impact of all sources of bias and confounding are likely complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was motivated by reviews and meta-analyses reporting different results by study design ( e.g. , [ [7] , [8] ]) and the recent availability of data on talc recall in the prospective Sister's Study [ 13 ]. Realistically, the impact of all sources of bias and confounding are likely complex.…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies have consistently reported no overall association and no exposure-response relationship between perineal talc use and ovarian cancer risk overall. Also, experimental studies do not support a causal association [ 7 , 28 ]. Our analysis, using data from the Cramer et al [ 15 ] case-control study, demonstrates that recall bias alone may have a large impact on risk estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, some studies support an opposing perspective [ 37 , 38 , 39 , 40 ]. While certain studies have explored the link between talc exposure and ovarian cancer [ 30 , 41 ], there has been insufficient research on the tissue specific effects on the female genital system. In particular, the molecular and genetic processes associated with exposure to a cosmetic ingredient and the initial stages of cancer development have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%